PENGEMBANGAN MEDIA PEMBELAJARAN IPA MENGGUNAKAN COCO DIORAMA BERBASIS LIMBAH SABUT KELAPA PADA MATERI SIKLUS AIR DI KELAS V SDN 060800 MEDAN AREA - Refi Yulina; Zainuddin Muchtar; Winara; Laurensia Masri; Lidia Simanihuruk (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop a science learning media in the form of coco diorama that utilizes coconut fiber waste in the water cycle material for fifth grade elementary school students, and to determine the level of validity, practicality, and effectiveness of the media. This study applies the 4D development model (Define, Design, Development, Disseminate). The subjects in this study were 21 fifth grade students of SDN 060800 Medan Area. Data collection techniques were carried out through interviews, observations, questionnaires, and tests. The data analysis used qualitative and quantitative approaches. The results of the study showed that: (1) the coco diorama learning media was considered valid based on the validation results of material experts by 94% and media experts by 89% with the category "very feasible"; (2) the coco diorama learning media was declared practical based on teacher responses with a percentage of 92% in the category "very practical"; and (3) the coco diorama learning media was proven effective in improving student learning outcomes. This can be seen from the average pre-test score of 46.9% which increased to 88.3% in the post-test. In addition, at the dissemination stage there was also an increase in learning outcomes from 47.0% to 87.0% with an N-Gain value of 0.764 or 76.4% which is included in the high category. Thus, the coco diorama learning media based on coconut fiber waste is proven to be valid, practical, and effective for use in science learning on the water cycle material in elementary schools, and is able to significantly improve student learning outcomes outcomes